Living the fancy life : understanding guests preferences in a luxury hotel context - Sottomayor, Maria Meyrelles do Souto Almeida de (2022)
The recent years have seen substantial growth in the service industry, especially regarding luxury services. Moreover, more and more customers in this sector are looking to spend their money on experiences rather than tangible goods. This fact has had a very positive impact on the luxury hotel sector. This dissertation aims to understand what is most valued by luxury hotel customers regarding hotel attributes, services, and experiences offered. The secondary objective is to understand whether the reason for traveling 8(either leisure or business) and the age of customers impact their preferences. By conducting three Focus Groups, five main themes were identified: Hotel, Luxury, Experience, Room, and Holiday. It was possible to divide these themes into two distinct groups: The tangible and the intangible. From the tangibles, we have the theme "Room," The remaining four themes belong to the intangibles group. It was then possible to understand that the room is a fundamental attribute for all customers. There has been an increasing shift from the search for the tangible to the intangible, and luxury hotel customers move more by the sensations a hotel can provide. This dissertation aims to help managers of luxury hotels to make them understand what the majority of customers are looking for.